2009
DOI: 10.1175/2009jcli2954.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Climate Change in the Tropical Midtroposphere over East Africa from Glacier Shrinkage on Kilimanjaro

Abstract: Slope glaciers on Kilimanjaro (ca. 5000-6000 m MSL) reached their most recent maximum extent in the late nineteenth century (L19) and have receded since then. This study quantifies the climate signal behind the recession of Kersten Glacier, which generates information on climate change in the tropical midtroposphere between L19 and present. Multiyear meteorological measurements at 5873 m MSL serve to force and verify a spatially distributed model of the glacier's mass balance (the most direct link between glac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
239
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 128 publications
(252 citation statements)
references
References 56 publications
10
239
0
1
Order By: Relevance
“…Hastenrath and Kruss (1992) proposed that continued glacier recession from 1963 until 1987 was mainly caused by an increase in atmospheric humidity that forced more efficient use of available energy to increase melting. More recently, Mölg et al (2003), Kaser et al (2004), Cullen et al (2006), and Mölg et al (2009) proposed that the 20th century recession of Kilimanjaro's glaciers was driven entirely by decreasing precipitation and atmospheric drying. As part of the proof, Mölg and Hardy (2004), Cullen et al (2007) and Mölg et al (2008Mölg et al ( , 2009 showed, using energy and mass-balance modelling, that the retreat of Kilimanjaro glaciers since 2000 reflects atmospheric aridity and the associated increased receipt of solar radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Hastenrath and Kruss (1992) proposed that continued glacier recession from 1963 until 1987 was mainly caused by an increase in atmospheric humidity that forced more efficient use of available energy to increase melting. More recently, Mölg et al (2003), Kaser et al (2004), Cullen et al (2006), and Mölg et al (2009) proposed that the 20th century recession of Kilimanjaro's glaciers was driven entirely by decreasing precipitation and atmospheric drying. As part of the proof, Mölg and Hardy (2004), Cullen et al (2007) and Mölg et al (2008Mölg et al ( , 2009 showed, using energy and mass-balance modelling, that the retreat of Kilimanjaro glaciers since 2000 reflects atmospheric aridity and the associated increased receipt of solar radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering mass fluxes, the undeniable fact that melting occurred in former centuries is based on the observation of "strong and widespread melting" in the 1880s by early scientists (6), and this is consistent with the physically based mass-flux reconstruction for that time (2). Therefore, concluding "the absence of surface melting" on Kilimanjaro before recent decades (1) is invalid.…”
mentioning
confidence: 98%
“…We think it is essential to acknowledge these details, because they provide an exceptional opportunity to unravel changes of multiscale linkages in the climate system (sections 6 and 7 in ref. 2).…”
mentioning
confidence: 99%
See 2 more Smart Citations